2020
DOI: 10.21203/rs.3.rs-46035/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How fear and collectivism influence public's preventive intention towards COVID-19 infection: A study based on big data from the social media

Abstract: Background: Despite worldwide calls for precautionary measures to combat COVID-19, the public's preventive intention still varies significantly among different regions. Exploring the influencing factors of the public's preventive intention is very important to curtail the spread of COVID-19. Previous studies have found that fear can effectively improve the public's preventive intention, but they ignore the impact of differences in cultural values. The present study examines the combined effect of fear and coll… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…Using the cultural groupings of countries based on the World Values Survey (Inglehart & Welzel, 2005), Mayer et al (2020) find that countries in two cultural families-Confucian and South Asian-seem particularly successful in containing Covid-19 morbidity rates. In a country-specific study, Huang (2020) find that collectivism and fear of Covid-19 together perhaps drive people's preventive intentions in China. Other studies too have highlighted the seemingly deleterious role of individualism within US (Bazzi et al, 2021) as well as across countries (Maaravi et al, 2021;Webster et al, 2021).…”
Section: Literature Review and Hypothesesmentioning
confidence: 94%
“…Using the cultural groupings of countries based on the World Values Survey (Inglehart & Welzel, 2005), Mayer et al (2020) find that countries in two cultural families-Confucian and South Asian-seem particularly successful in containing Covid-19 morbidity rates. In a country-specific study, Huang (2020) find that collectivism and fear of Covid-19 together perhaps drive people's preventive intentions in China. Other studies too have highlighted the seemingly deleterious role of individualism within US (Bazzi et al, 2021) as well as across countries (Maaravi et al, 2021;Webster et al, 2021).…”
Section: Literature Review and Hypothesesmentioning
confidence: 94%
“…Research on long-term attitudes and behaviours has frequently shown that personality variables, such as different traits, personal values or convictions often explain substantial variance in the prediction of health-related behaviours (Cockerham et al, 2006;Raynor & Levine, 2009;Vollrath & Torgersen, 2008). With regard to emotional and behavioural responses to COVID-19, risk aversion (Nikolov et al, 2020), trust in politicians and in science (Lalot et al, in press;Kreps & Kriner, 2020) as well as collectivism (Huang et al, 2020;Pei et al, 2020) have been identified as relevant predictors. To be able to disentangle potential framing effects from possibly confounding variables, we integrated these variables as personality-related covariates.…”
Section: Control Variablesmentioning
confidence: 99%
“…Especially when increased security becomes socially normative, acting in line with group norms and for the safety of others may not feel like losing freedom to the same extent as it would to people in a more individualistic cultural context. Consistent with this possibility, some initial evidence from the COVID-19 pandemic suggests that higher levels of collectivism were related to greater support of restrictive policies (Pei et al, 2020), greater compliance with mask and social-distancing mandates (Bazzi et al, 2021; Huang et al, 2020; Lu et al, 2021), lower rates of mental-health distress (Germani et al, 2020; but see also Kowal et al, 2020), and lower rates of virus transmission and death (Pei et al, 2020).…”
Section: Caveats Cautions and Considerationsmentioning
confidence: 91%